Analisis Kemampuan Siswa Kelas V SD dalam Merencanakan dan Mengevaluasi Penyelidikan Ilmiah Materi Organ Pernapasan - Kinanti Putri, Vincentia Vania; Rusmawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science literacy is an essential competency that needs to be developed from elementary school, particularly in planning and evaluating scientific investigations as emphasized in the Programme for International Student Assessment (PISA) framework. However, learning science in elementary schools is often still dominated by conceptual teaching, resulting in limited opportunities for students to engage in scientific investigations. This study aimed to analyze the ability of fifth-grade elementary school students to plan and evaluate scientific investigations on the topic of the respiratory system. The study employed a quantitative descriptive method and was conducted at an elementary school in Semarang Regency. The participants were all 54 fifth-grade students, selected using a saturated sampling technique. Data were collected using a multiple-choice test developed based on PISA science literacy indicators, including identifying scientific questions, designing investigationsancang and evaluating investigations, interpreting data, and drawing conclusions. The data were analyzed using descriptive statistics to obtain mean scores, percentages, and ability categories. The results showed that students’ ability to plan scientific investigations was in the moderate category with an average score of 70.74, while their ability to evaluate scientific investigations was in the good category with an average score of 83.10. These findings indicate that students are relatively better at interpreting data and drawing conclusions than at planning investigation procedures. Therefore, science learning in elementary schools should emphasize balanced scientific inquiry activities to enhance students’ science literacy skills in accordance with the PISA framework.